Work history and mortality risks in 90 268 US radiological technologists. Issue 12 (22nd May 2014) - Liu, Jason J; Freedman, D Michal; Little, Mark P; Doody, Michele M; Alexander, Bruce H; Kitahara, Cari M; Lee, Terrence; Rajaraman, Preetha; Miller, Jeremy S; Kampa, Diane M; Simon, Steven L; Preston, Dale L; et al.
Abstract : Objectives: There have been few studies of work history and mortality risks in medical radiation workers. We expanded by 11 years and more outcomes our previous study of mortality risks and work history, a proxy for radiation exposure. Methods: Using Cox proportional hazards models, we estimated mortality risks according to questionnaire work history responses from 1983 to 1989 through 2008 by 90 268 US radiological technologists. We controlled for potential confounding by age, birth year, smoking history, body mass index, race and gender. Results: There were 9566 deaths (3329 cancer and 3020 circulatory system diseases). Mortality risks increased significantly with earlier year began working for female breast (p trend=0.01) and stomach cancers (p trend=0.01), ischaemic heart (p trend=0.03) and cerebrovascular diseases (p trend=0.02). The significant trend with earlier year first worked was strongly apparent for breast cancer during baseline through 1997, but not 1998–2008. Risks were similar in the two periods for circulatory diseases. Radiological technologists working ≥5 years before 1950 had elevated mortality from breast cancer (HR=2.05, 95% CI 1.27 to 3.32), leukaemia (HR=2.57, 95% CI 0.96 to 6.68), ischaemic heart disease (HR=1.13, 95% CI 0.96 to 1.33) and cerebrovascular disease (HR=1.28, 95% CI 0.97 to 1.69). No other work history factors were consistently associated with mortality risks from specific cancers or circulatory diseases, or other conditions. Conclusions: Radiological technologists who began working in early periods and for more years before 1950 had increased mortality from a few cancers and some circulatory system diseases, likely reflecting higher occupational radiation exposures in the earlier years.